Millet nutrient use efficiency as affected by natural soil fertility, mineral fertilzer use and rainfall in the West African Sahel - Fofana, B.; Wopereis, Marco C.S.; Bationo, B. André; Breman, H.; Mando, A. (Springer, 2008)
Field experiments were designed to investigate the effectiveness of integrated soil fertility management (ISFM), comparing fertilizer use efficiency and its impact on millet, cultivated close to the homestead ( infields ) and away from the homestead ( outfields ). Millet yields and response to N (0, 30, and 60 kg ha?1) and P (0, 15, and 30 kg ha?1) were determined on nine infields and nine outfields over a period of 3 years (from 1999 to 2001) in the southern Sahel of Niger. Rainfall was 650, 470, and 370 mm during the three successive years, interaction between decreasing rainfall and millet yield performance was also analyzed. While soil organic carbon (1.5 g kg?1 on outfields and 1.6 g kg?1 on infields) and pH-H2O (4.8 on outfields and 5.1 on infields) were comparable, total-N, plant available P (measured as P-Olsen and P-Bray), and exchangeable Ca, K, and Mg levels were higher on infields as compared to outfields. Without fertilizer, average grain yield (GY) and stover yield obtained on infields were three times as high as on outfields. GY across years and fertilizer treatments was higher on infields as compared to outfields (P < 0.001). Average yield was 800 kg ha?1 on outfields and 1,360 kg ha?1 on infields (P < 0.001). On outfields, average GY was stagnant over the 3-year experimental period. Despite declining rainfall, millet GY across all treatments gradually increased over time on infields (P < 0.001). P fertilization alone resulted on both field types to steadily and substantial yield increases while yield response to N fertilization was only obvious when fertilizer P was applied. With no fertilizer applied, N uptake on infields (19 kg N ha?1) was more than twice as high as on outfields (7 kg ha?1), and P uptake was four times higher on infields (3 kg ha?1) than on outfields (0.8 kg ha?1). Indigenous soil N supply was on average 24 kg N ha?1 on outfields and 46 kg N ha?1 on infields. Average value for indigenous soil P supply was 4 kg P ha?1 on infields and 2 kg ha?1 on outfields. Apparent recovery of fertilizer N applied varied considerably among treatments and ranged from 17 to 23% on outfields and 34 to 37% on infields (P < 0.001). Average apparent recovery of fertilizer P applied was significantly higher (P < 0.001) on infields (31%) than on outfields (18%) over the 3-year growing period, illustrating ISFM-induced positive effect on millet nutrient N and P use. Results indicate higher inherent soil fertility, underline ISFM-induced drought tolerance of soils on infields as compared to outfields, and highlight the crucial role of fertilizer P (especially on outfields) for millet production. These call for site-specific nutrient management and support, even under low rainfall conditions, the potential value of fertile infields for efficient and productive external input use and sustainable millet production in West African Sahel.